1997
DOI: 10.1038/sj.onc.1201249
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric oncoprotein E2a-Pbx1 induces apoptosis of hematopoietic cells by a p53-independent mechanism that is suppressed by Bcl-2

Abstract: The chimeric oncoprotein E2a-Pbx1 results from fusion of the E2A and PBX1 genes following t(1;19) chromosomal translocations in B cell precursor acute leukemias. Experimentally B cell progenitors do not tolerate constitutive expression of E2a-Pbx1 which contrasts with transformation of several other cell types following its stable expression both in vitro and in vivo. To further investigate the e ects of E2a-Pbx1 on the B cell progenitors, we conditionally expressed E2a-Pbx1 under control of a metal response e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Several genes implicated in oncogenesis have been shown to induce either transformation or apoptosis, including c-myc (Askew et al, 1991, Evan et al, 1992, activated N-ras (Darley et al, 1997) andcjun (Bossy-Wetzel et al, 1997), often in a cell-type dependent fashion. Expression of other leukemiaassociated chimeric oncoproteins, such as E2A/PBX1 (Smith et al, 1997) and PML/RARa (Ferrucci et al, 1997) can induce apoptosis of hematopoietic cells, yet their expression is clearly tolerated in the leukemic cell. We have similarly found that the myeloid cell lines 32Dc13, FDCP-1, and HL-60 do not tolerate constitutive expression of AML1/ETO (Frank et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Several genes implicated in oncogenesis have been shown to induce either transformation or apoptosis, including c-myc (Askew et al, 1991, Evan et al, 1992, activated N-ras (Darley et al, 1997) andcjun (Bossy-Wetzel et al, 1997), often in a cell-type dependent fashion. Expression of other leukemiaassociated chimeric oncoproteins, such as E2A/PBX1 (Smith et al, 1997) and PML/RARa (Ferrucci et al, 1997) can induce apoptosis of hematopoietic cells, yet their expression is clearly tolerated in the leukemic cell. We have similarly found that the myeloid cell lines 32Dc13, FDCP-1, and HL-60 do not tolerate constitutive expression of AML1/ETO (Frank et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in developing lymphocytes in these mice indicated a cytotoxic e ect of E2A-PBX1 expression in primary B (and T) lineage cells. Importantly, it has been demonstrated that E2A-PBX1 does indeed activate apoptosis in primary and transformed pre-B cells and that this cell death can be abrogated by expression of the anti-apoptotic gene Bcl-2 (Smith et al, 1997). Unlike Myc and E1A, E2A-PBX1-mediated programmed cell death is p53-independent (Smith et al, 1997).…”
Section: Mouse Models For Human E2a-pbx1 Pre-b Allmentioning
confidence: 99%
“…Coactivation of Meis1 and HoxA9 in mouse myeloid leukemia provides one example of cooperating oncogenes that encode transcription factors that bind each other and may need to heterodimerize as part of their oncogenic mechanism (Nakamura et al, 1996). Considering the possibility that E2a-Pbx1 might also require a second cooperating oncogene expressed only in t(1;19) cells and that E2a-Pbx1 induces apoptosis when expressed in non-t(1;19) pre-B ALL cell lines (Smith et al, 1997), we choose to attempt to identify genes that are uniquely transcribed in the t(1;19) subset of pre-B ALL. Among the genes discovered, EB-1 was transcriptionally activated exclusively and invariantly both in pre-B cell lines and in pre-B ALL marrow aspirates containing the t(1;19).…”
Section: Introductionmentioning
confidence: 99%